Automatic chicken feeder / Mohamad Adib Mohamad Amini & Nuralya Aiman Abdur Rahman - Mohamad Amini, Mohamad Adib; Abdur Rahman, Nuralya Aiman (2015)
Malaysians nowadays prefer devices or technology that can obtain benefits to our mother nature as in today; we are practicing a healthy environment in our surrounding for a better future for our next generation. Hence, in order to comply the environmental friendly device, a chicken feeder is proposed to be our project. nowadays chicken feeders are mostly based on manual where when the chickens will have to step onto the chicken feeder's treadle platform, and it will manually bring up the feeder lid until the chickens step out of it, but eventually, for the first timer, maybe one or two chicken might get injured because they had been eating from aside, when other chickens step out, the other chickens at the aside will get neck injured because of the lid closed suddenly. Besides, chickens in Malaysia mostly are having bad eating habit which means eating without stop most of the time. So by having it automatically, the chicken will be force to be eating at certain time so that we can control them from being overweight. So, by doing it automatically, the dispenser lid will open at given or desired time and the chickens will automatically attracted to the feeder or dispenser and continue to eating. The project of ours, the chicken feeder system works as it provides a very healthy lifestyle of the chickens' proper meal time as it will only drop the food at the certain desired time. Moreover, there will be less interaction in between the chickens and the human as it leads to a natural growth and the decreasing of the death rate of the chickens in Malaysia. This project is using The Arduino Software to complete the coding part while the simulation was done by using the Proteus.